Free movement of workers within the EU - Konjević, Tena (Zbornik znanstvenih razprav (Pravna fakulteta. 1991), 2023)
The article analyses the application of the principle of free movement of workers within the European Union, focusing on the challenges arising from implementing transitional arrangements that restricted this freedom for the Central and Eastern European (CEE) countries’ nationals because of the concerns about mass migration and its po- tential impact on the labour market. The article aims to provide an overview of these reasons, scrutinising their proportionality and justification. Additionally, it examines the impacts of those transitional provisions, which have resulted in unequal EU citizenship rights and have stimulated the CEE workers’ predominant occupation in low-wage sectors of the labour market. Furthermore, the emergence of prejudice based on cultural differences towards the CEE workers has influenced Western EU employers’ preference for ‘good workers’ from the CEE countries, often attributed to the strong work ethic and willingness of the CEE workers to fill workforce gaps in less desirable jobs. To interrogate this matter and to determine whether the preference of the CEE workers arises from solidarity or some other interest, empirical research was conducted on a sample of Croatian nationals working in Germany. By its qualitative and quantitative approach, the article contributes to understanding the implications and dynamics surrounding the freedom of movement for workers within the EU, with a specific focus on the position of the CEE countries’ nationals. It explores the motives behind the implementation of transitional arrangements, examines their consequences for the EU labour market, and investigates the factors influencing Western employers’ preferences toward the CEE mobile workers.
Keywords: delavci; delovno pravo; ekonomske migracije; Evropska unija; pravice delavcev; prost pretok; trg dela